Laparoendoscopic single-site surgical cystectomy of a twisted ovarian dermoid cyst during early pregnancy: A case report and literature review - Dah-Ching Ding; Yu-Hsiun Chang (Wolters Kluwer Medknow Publications, 2016)
In pregnancy, the most frequently discovered ovarian tumor is mature cystic teratomas. Acute ovarian torsion in a pregnant patient is rare and is difficult to diagnose. Recent studies have demonstrated that laparoscopy during pregnancy is safe and confers many advantages over laparotomy. We report a patient with acute ovarian teratoma torsion treated with ovarian cystectomy via a single-port laparoscopy and review of the literature. A 17-year-old woman, gravida 1, in her 12th week of pregnancy, came to our emergency room with severe abdominal pain and nausea. Torsion of ovarian teratoma (5 cm in diameter) was suspected. The patient underwent emergent laparoendoscopic single-site surgery (LESS) under general anesthesia, and the detorsed cyst was successfully excised and removed intact through the single port. This was enabled by the endobag technique, thus preventing spillage of the cyst content into the abdominal cavity. The fetus tolerated surgery well without complications and was term delivered uneventfully. The literature review revealed that the advantages of using LESS in pregnant patients are that this technology is safe for both the mother and the fetus, and it allows easy removal of specimen. However, it also has several drawbacks: technically challenging and limitation of working space. In conclusion, LESS seems to be a viable alternative to multiport laparoscopic surgery for the treatment of adnexal masses in pregnancy.